Academic leadership and the use of ICTS in the environment of the COVID-19 pandemic (Enlace UIC: Revista de Investigación de la División de Posgrados de la Universidad Intercontinental, 2022)
This article is based on the confinement caused by the COVID-19 pandemic, restricting essential activities for Mexican society; among these, the educational one. That is why, the main theme is the role of the teacher as a leader, immersed in this new normality, with the essential purpose of promoting the development of learning, and the role it plays in students and in their academic practice, in the design, operation and evaluation where the use of the internet as an educational tool is located. In addition to understanding the needs andalumproblems faced by education actors, which must be endowed with essential and relevant resources for mastering the new information and communication technologies (ICT), applied to technologies. of learning and knowledge (TAC), developing their necessary educational skills, already acquired before the pandemic, without neglecting the socio-emotional and disciplinary ones such as: self-regulation, motivation, determination, teamwork, adaptability, perseverance and tolerance, assertive communication and conflict resolution. The leadership that teachers develop in this regard must be a direct function of the capacities and aptitudes of the students so that, in this new normal, the power of adaptation of both actors, in the teaching and learning processes, is achieved efficiency required to meet institutional and operational objectives.
Keywords: learning; educational skills; leadership; new normal